Locus of Control, Job Insecurity and Work Engagement: A Comparative Study Among Healthcare Workers Engaged on Regular and Outsourced Basis in an Institute of National Importance in Delhi - Mohammad, Kausar; Siddharth, Vijaydeep; Hakim Choudhary, Abdul; Verma, Arun; Mehmood, Khalid; Raj, Charan; Sharma, DK (Department of Management, Faculty of Economics and Business, Brawijaya University, 2026)
Employee engagement plays a critical role in organizational success, as engaged employees tend to invest more time, assume additional responsibilities, support colleagues, and demonstrate higher levels of job satisfaction, performance, and organizational commitment. However, with the increasing shift toward outsourcing, its implications for work engagement remain insufficiently explored. This analytical correlational study, grounded in established theoretical perspectives, was conducted at a premier healthcare institution of national importance in New Delhi to examine levels of work engagement and job insecurity among regular and outsourced employees, as well as their association with locus of control—a construct reflecting individuals’ perceived control over significant life events. The study population consisted of 576 outsourced and 1,099 regular employees, with a final sample of 562 respondents, including 166 regular and 396 outsourced employees. The findings indicate that work engagement is higher among outsourced employees and increases with internal locus of control, age, experience, and lower job insecurity, while it is not influenced by gender or education level. Locus of control does not vary significantly with age, experience, gender, or education. Additionally, outsourced employees exhibit higher internal locus of control and lower job insecurity. Job insecurity decreases with age, experience, and internal locus of control, is not affected by education level, and is higher among female employees.